How to influence the continuous usage intention of game-based Internet public welfare users? An empirical analysis based on SEM and fsQCA - Jing Liu; Xiaohan Chen; Xuwei Zhou; Jianxiang Wei; Chengzhi Liu (PLoS ONE, 2025)
This study focuses on UTAUT and integrates the D&M, SDT, and SET models to explore the factors influencing continuous usage intention in the context of gamified online public welfare. By applying structural equation modeling and fuzzy-set qualitative comparative analysis to 389 valid survey samples, this study identifies that public value, leisure and entertainment, and self-payment significantly influence users’ continuous usage intention. Furthermore, game design and tool convenience, along with subjective norms, are key drivers of these three factors. In contrast, gaming convenience and social factors have limited impact on user engagement. The findings reveal three enhancing configurations—functionality-driven, comprehensive support, and pure public value paths—and four inhibiting configurations—complete disengagement, social impact without incentives, convenience without enjoyment, and engagement without enjoyment paths. The crucial role of subjective norms is found to be consistently significant in both the SEM and fsQCA results, making it a key factor in promoting user engagement in gamified public welfare activities. This research contributes to the theoretical understanding of user participation in game-based charity activities and provides insights for improving user retention. Its originality lies in the integration of SDT and SET models alongside D&M and UTAUT, as well as the use of mixed methodologies to examine the multifaceted drivers of continuous usage intention.